Towards a standardized e-assessment system: motivations, challenges and first findings - AL-Smadi, M.; Guetl, Christian; Helic, D. (Association for the Advancement of Computing in Education, 2009)
“Global Learning” with shared learning contents,resources, activities and goals is one of the contributions ofGlobalization. With the capability to use new Informationand Communication Technologies (ICT) it is a bit easier tohave a technology based learning systems that enable learnersto share the learning resources and possibilities. As aresult many Learning Management Systems (LMS) weredeveloped with divers of platforms and approaches. Consequently,sharing learning resources and components hasbecome a major challenge. E-assessment as a primary activityof any LMS is facing the same challenges and problems.In order to stand on this challenge people in the field oftechnology enhanced learning have recommended that LMSshould conform to specific standards. This paper discusesthis challenge, the consequences and limitations of standardsin the modern learning settings. Moreover, it shows aservice oriented framework for assessment which aims tomake the e-assessment systems flexible and also to initiatethe term of “Global Learning Assessment” with the possibilityof sharing the e-assessment system components.